Lexical Complexity of Decision-Making Writing Tasks: Form-focused Guided Strategic Planning - Mahdavirad, Fatemeh (Widya Mandala Surabaya Catholic University, 2016)
The present study is an attempt to investigate the effect of form-focused guided strategic planning on lexical complexity of learners’ performance in writing tasks. The twenty intermediate level participants of the study performed an unplanned and then a planned decision-making task. In the planned task condition, the participants were provided with form-focused guided strategic planning which contained detailed instructions about how to plan, by being instructed to focus on form. The guidance included an explanation of the necessary structural and lexical patterns employed to express the learners’ views while developing a comparison-and-contrast paragraph in each task. The results of the statistical analysis indicated that the participants produced a written product with a greater lexical complexity in their performance of the task in the form-focused strategic planning condition. The findings emphasize the importance of guided strategic planning as a task condition in syllabus design for task-based language teaching and the necessity of incorporating this task feature for accomplishing lexical complexity in decision-making writing tasks.